Acute and late toxicity patterns of moderate hypo-fractionated radiotherapy for prostate cancer: A systematic review and meta-analysis. (May 2023) - Sinzabakira, F.; Brand, V.; Heemsbergen, W.D.; Incrocci, L.
Highlights: Moderate hypofractionated (HF) radiotherapy is becoming the new standard in radiotherapy for prostate cancer patients. It is established as safe, but it might be associated with increased acute toxicity levels. Using PRISMA guidelines, we conducted a systematic review for studies published until June 2022. We identified 17 prospective studies reporting acute toxicity of moderate hypofractionation (2.5–3.4 Gy/fraction). A meta-analysis was done for 10/17 studies with a control arm. We used Cochrane bias assessment and Newcastle-Ottawa bias assessment tools for randomized controlled trials (RCTs) RCT and non-RCTs, respectively. Pooled results showed that acute grade ≥ 2 gastro-intestinal (GI) toxicity was relatively increased by 6.3 % (95 % CI = 2.0 %–10.6 %) in HF group, acute grade ≥ 2 Genito-urinary (GU) in HF was not significantly increased. The overall risk of bias assessment revealed a low risk in the meta-analysis of included studies. Available data suggest increased GI symptoms in the acute phase, needing adequate monitoring and management. Abstract: Introduction: Moderate hypofractionated (HF) radiotherapy is becoming the new standard in radiotherapy for prostate cancer patients. It is established as safe, but it might be associated with increased acute toxicity levels. We conducted a systematic review on moderate HF to establish acute toxicity levels and their required clinical management; late toxicity was reported as a secondary outcome. Material and methods: Using PRISMA guidelines, we conducted a systematic review for studies published until June 2022. We identified 17 prospective studies, with 7796 localised prostate cancer patients, reporting acute toxicity of moderate hypofractionation (2.5–3.4 Gy/fraction). A meta-analysis was done for 10/17 studies with a control arm (standard fractionation (SF)), including evaluation of late toxicity rates. We used Cochrane bias assessment and Newcastle-Ottawa bias assessment tools for randomized controlled trials (RCTs) RCT and non-RCTs, respectively. Results: Pooled results showed that acute grade ≥ 2 gastro-intestinal (GI) toxicity was increased by 6.3 % (95 % CI for risk difference = 2.0 %–10.6 %) for HF vs SF. Acute grade ≥ 2 Genito-urinary (GU) and late toxicity were not significantly increased. The overall risk of bias assessment revealed a low risk in the meta-analysis of included studies. Data on management of toxicity (medication, interventions) was only reported in 2/17 studies. Conclusion: HF is associated with increased acute GI symptoms, needing adequate monitoring and management. Reports on toxicity management were very limited. Pooled late GI and GU toxicity showed similar levels for SF and HF.